Psychological profile of Hungarian national young ice hockey players - Geczi, G.; Toth, L.; Sipos, K.; Fügedi, B.; Dancs, H.; Bognar, J. (Kinesiology, 2009)
As regards psychological determinants, self-determination, sacrifice, and coping with pressure are all necessary mental skills for success in ice hockey. The aims of this study were to identify those psychological background factors for three age groups of the national ice hockey teams (U16, U18, U20) that are of the most importance. It was also the purpose of this study to determine the age-related psychological differences which may play a long-term role in the ice hockey players` careers. Altogether 95 elite male ice hockey players filled out CSAI-2, ACSI-28, STPI-Y self-evaluation questionnaires. ANOVA showed no differences among the age groups with the exception of the trait anger scale results.